Potocyzmy i wulgaryzmy w powieści Jáchyma Topola »Strefa cyrkowa« - Taboł, Sebastian (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2016)
Article answers the question: What are the functions in the novel Poplar vulgar and colloquial words. The use of these words is certainly thought-treatment by the author. The use of these tokens is aware of mediocrity reality in which man does not have to try to speak properly, carefully, beautifully and efficiently. If reality is not acceptable, the sender is released from the culture of the language, attention to accuracy of expression, located in the appropriate scale of compliance with the standard language. Setting heroes is gray, ugly, therefore the characters speak everyday, expressively motivated by which Topol also convinces the reader of the hopelessness of the world in which they found themselves heroes. Profanity and colloquialism have a definite, clear and powerful method for evaluating the world and people. Language transfer, saturated with this type of lexemes is highly expressive and emotional.
Keywords: Czech literary; lexeme; colloquial style; Topol; profanity